Causal relationship between the immune phenotype of monocytes and myasthenia gravis: A Mendelian randomization study - Jing Dong; Rui-sheng Duan; Peng Zhang (Heliyon, 2024)
Background: Monocytes play an essential role in developing autoimmune diseases; however, their association with myasthenia gravis (MG) development is unclear. Methods: We performed a two-sample Mendelian randomization analysis to assess the causal relationship between monocyte-associated traits and MG, reviewing summary statistics of genome-wide association studies (GWAS). Results: Using the inverse variance weighted method, the following were found to be causally associated with MG: HLA-DR on monocytes (OR, 1.363; 95% CI, 1.158–1.605; P = 2E-04), HLA-DR on CD14+ monocytes (OR, 1.324; 95% CI, 1.183–1.482; P = 1.08E-06), HLA-DR on CD14+CD16− monocytes (OR, 1.313; 95% CI, 1.177–1.465; P = 1.07E-06), CD40 on monocytes (OR, 1.135; 95% CI, 1.012–1.272; P < 0.05), CD40 on CD14+CD16− monocytes (OR, 1.142; 95% CI, 1.015–1.285; P < 0.05), CD40 on CD14+CD16+ monocytes (OR, 1.142; 95% CI, 1.021–1.278; P < 0.05), CD64 on CD14+CD16+ monocytes (OR, 1.286; 95% CI, 1.019–1.623; P < 0.05). Conclusions: The present study suggests a causal relationship between the upregulation of CD40, HLA-DR, and CD64 on monocytes and the development of MG. Altered monocyte function may potentially be a risk factor for MG and a therapeutic target.